The Allure of Professionalism: Teacher Candidate Subjectivity and Resistance in Neoliberal Times - Kaszuba, Adam (Critical Education)

(untitled) (Institute for Critical Education Studies / UBC, 2025)
Multiple discourses circulate in society which construct a vision of what professionalism looks like for teachers. When these discourses are put into practice in initial teacher education programs, teacher candidates feel compelled to integrate them without critically examining their underlying assumptions. Based on a Foucauldian framework, this study explores how teacher candidates in an Ontario Faculty of Education interacted with the language of dominant discourses as they constructed a collective identity and practice while participating in voluntary, emergent learning communities. Three discourses of professionalism emerged in the practices of the candidates: the discourse of passion, of mental health and well-being, and of safety. Through notions such as best practices and ‘truth acts’, I discuss how the discourses shape the candidates’ subjectivity, and in doing so, limit possibilities for resistance.